1984
DOI: 10.1111/j.1600-0676.1984.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver biopsy lesions in early autoimmune (“lupoid”) chronic active hepatitis

Abstract: ABSTRACT— We studied two female patients with autoimmune (“lupoid”) chronic active hepatitis whose liver biopsies at initial presentation showed the unusual features of an acute hepatitis. Centrilobular hepatocyte swelling and multinucleation, acidophilic degeneration, cholestasis, mild fatty change and bile duct damage in one case resembled lesions of non‐A, non‐B hepatitis. Lobular and portal infiltrates of plasma cells with piecemeal necrosis suggested transition to chronicity as well as an autoimmune compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 10 publications
(6 reference statements)
0
22
0
Order By: Relevance
“…To date, no standardised definition or acceptable diagnostic criteria have been established for the acute presentation of AIH, although this entity has long been recognised 10 66. Liver biopsy is crucial to diagnose AIH and guide treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no standardised definition or acceptable diagnostic criteria have been established for the acute presentation of AIH, although this entity has long been recognised 10 66. Liver biopsy is crucial to diagnose AIH and guide treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Lefkowitch et al fi rst reported AIH cases presenting histologically acute hepatitis. 19 In a Japanese nationwide survey study, 5.6% of patients with AIH were found to have a feature of acute hepatitis upon histological examination. 20 Nikias et al reported that lobular hepatitis is an important histological feature in AIH with an acute presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Lefkowitch et al . first reported two AIH cases presenting histologically acute hepatitis 1 . Abe et al .…”
Section: Review Of the Reported Cases Of Acute Presentation Of Aihmentioning
confidence: 99%